2021
DOI: 10.1186/s12866-021-02385-x
|View full text |Cite
|
Sign up to set email alerts
|

A new strain of Volutella citrinella with nematode predation and nematicidal activity, isolated from the cysts of potato cyst nematodes in China

Abstract: Background Plant parasitic nematodes (PPNs) are responsible for causing many plant diseases and are extremely difficult to control at present. Currently, due to the negative effects of chemical agents on the environment and human health, the development of new biological pesticides has become an important part of plant nematode control. Nematophagous fungi refers to a class of fungi that kill plant nematodes. Notably, a large number of nematophagous fungi resources remain to be studied. The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…Cada suelo alberga su propia diversidad de comunidades microbianas que desempeñan un papel crucial en la defensa contra los fitopatógenos (Nwokolo et al, 2021). Por lo tanto, resulta fundamental descubrir nuevos agentes biológicos con potencial para desarrollar estrategias efectivas en el control de las enfermedades de las plantas (Quevedo et al, 2021;Zhang et al, 2021), mejorando así la calidad del suelo y las interacciones microbianas (Manohar et al, 2020). Se hace necesario aplicar un consorcio de bacterias y hongos capaces de producir compuestos nematicidas eficaces y respetuosos con el medio ambiente.…”
Section: Bacterias Endosimbióticasunclassified
“…Cada suelo alberga su propia diversidad de comunidades microbianas que desempeñan un papel crucial en la defensa contra los fitopatógenos (Nwokolo et al, 2021). Por lo tanto, resulta fundamental descubrir nuevos agentes biológicos con potencial para desarrollar estrategias efectivas en el control de las enfermedades de las plantas (Quevedo et al, 2021;Zhang et al, 2021), mejorando así la calidad del suelo y las interacciones microbianas (Manohar et al, 2020). Se hace necesario aplicar un consorcio de bacterias y hongos capaces de producir compuestos nematicidas eficaces y respetuosos con el medio ambiente.…”
Section: Bacterias Endosimbióticasunclassified
“…Zhang et al [ 110 ] reported that the fungus Volutella citrinella GUCC2219 exhibited a predation rate of 33% on the PWN after 72 h in vitro, and a fermentation broth of GUCC2219 was able to produce a mortality rate of 100% after the same period and under the same conditions.…”
Section: Microbes Against Plant-parasitic Nematodesmentioning
confidence: 99%
“…Recent studies on the biological control of A. bessyi are scarce, but Tülek et al [ 81 ] reported that the independent application of the bacterial symbiont Xenorhabdus bovienii and P. lilacinum were effective in suppressing the WTN, theorizing that the concomitant use of both BCAs could yield better results. Zhang et al [ 110 ] found that the fungus Volutella citronella GUCC2219 had a 59.45% predatory rate on the WTN and killed 100% of the nematodes after 72 h in vitro.…”
Section: Microbes Against Plant-parasitic Nematodesmentioning
confidence: 99%
“…The nematicidal activity of the T. harzianum and T. afroharzianum strains was evaluated through fermentation [ 39 ]. A new colonizing fungus ( Volutella citrinella GUCC2219) was obtained in Guizhou, isolated from G. rostochiensis cysts with predatory and nematicidal activities against three plant-parasitic nematodes ( Aphelenchoides besseyi , Bursaphelenchus xylophilus , and Ditylenchus destructor ) [ 40 ]. In summary, due to various geographical locations, the diversity of colonizing fungi in the soil, and planting methods, there are significant differences in colonizing fungi strains and dominant populations in regions where G. rostochiensis occurs, and these colonizing fungi often have different degrees of nematicidal activity.…”
Section: Introductionmentioning
confidence: 99%